Performance based algorithm for DWT and DCT for ISL. (2021) - Muthukumar, K.; VinothKumar, K.; Hepsiba, D.; Logeswaran, T.; Gunapriya, B.; Karthik, M.; Gokul, C.
Abstract: Communication plays a vital role in world. It is mainly carried out in from of speech or through non-verbal movements. Though the communication through speech is the origin for communication, other body expressions such hand movement and facial expressions also help to communicate our thoughts to others. The main aim of this research is as follows; The main objective of image compression is to reduce the size of data i.e used to represent a digital media in an efficient manner without causing major degradation to the quality of the image. To increase the efficiency and performance of digital data, image compression is used in various fields like security industries, federal government agencies and health industries. The reduced size may facilitate the quick transfer of the data over the communication channels. There are two types of compression methods. One is lossy and second is lossless compression. In lossless compression, no information is lost that is reduces bits by finding and eliminating redundancy. Lossy compression technique reduces size of data by finding non-essential information and destroys it. Therefore, the process of decreasing the size of data file is termed as data compression.